2004
DOI: 10.1007/s00213-003-1638-0
|View full text |Cite
|
Sign up to set email alerts
|

The plant-derived hallucinogen, salvinorin A, produces ?-opioid agonist-like discriminative effects in rhesus monkeys

Abstract: The naturally occurring hallucinogen salvinorin A produces discriminative stimulus effects similar to those of a high efficacy kappa-agonist in non-human primates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
87
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 16 publications
5
87
0
Order By: Relevance
“…administration of the kappa receptor antagonist, nor-BNI (4.5 nM), administered 60 min prior to salvinorin A. These findings are consistent with those of Butelman et al (2004). Together, these findings suggest that the discriminative stimulus effects of salvinorin A are mediated by kappa receptors.…”
supporting
confidence: 81%
See 3 more Smart Citations
“…administration of the kappa receptor antagonist, nor-BNI (4.5 nM), administered 60 min prior to salvinorin A. These findings are consistent with those of Butelman et al (2004). Together, these findings suggest that the discriminative stimulus effects of salvinorin A are mediated by kappa receptors.…”
supporting
confidence: 81%
“…Previous studies have demonstrated that salvinorin A substitutes in monkeys (Butelman et al 2004) or rats (Willmore-Fordham et al 2007) trained to discriminate the kappa agonist, U69,593, and that these effects are attenuated by KOP antagonists. The present results are consistent with these reports and extend these findings to a lower dose of the U69,593 and to another kappa agonist, U50,488.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…99 There has been only one report of behavioral testing of salvinorin A in nonhuman primates. 131 All subjects (n = 3) dose-dependently emitted ≥ 90% U69,593-appropriate responding after subcutaneous injection of salvinorin A (0.001 -0.032 mg/kg). Quadazocine (0.32 mg/kg), an opioid antagonist, blocked the effects of salvinorin A.…”
Section: Salvinorin Amentioning
confidence: 99%